The Influence of Quality of Raw Materials and Quality of Production Processes on Product Quality of MSMEs: A Moderation Analysis of Supplier Partnerships - Supriadi, Asep (International Journal of Islamic Business and Management Review, 2022)
The objective of this research is to analyze whether supplier partnerships can strengthen or weaken the effect of the quality of raw materials and the quality of the production process on the quality of the product to be achieved. These important variables are the quality of raw materials, the quality of the production process and partnerships with suppliers, which are very important for their realization. The method used in this study is a quantitative method using a sample of 110 MSME actors as respondents, then the data is processed with SmartPLS software, and analyzed. using Structural Equation Modeling (SEM). The findings of this study are that supplier partnerships do not moderate the effect of the quality of raw materials and the quality of the production process on product quality in SMEs in Serang City. The novelty of this research is to place partnerships with suppliers as a moderating variable, which in general in cases like this is training as a moderating variable, and the results are contrary to the results of research in general.